2023
DOI: 10.1038/s41598-023-29858-5
|View full text |Cite|
|
Sign up to set email alerts
|

A multiplexed, paired-pooled droplet digital PCR assay for detection of SARS-CoV-2 in saliva

Abstract: In response to the SARS-CoV-2 pandemic, we developed a multiplexed, paired-pool droplet digital PCR (MP4) screening assay. Key features of our assay are the use of minimally processed saliva, 8-sample paired pools, and reverse-transcription droplet digital PCR (RT-ddPCR) targeting the SARS-CoV-2 nucleocapsid gene. The limit of detection was determined to be 2 and 12 copies per µl for individual and pooled samples, respectively. Using the MP4 assay, we routinely processed over 1,000 samples a day with a 24-h tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…However, pooling samples can be challenging, and various factors can influence the sensitivity of the screening procedure. Studies have shown that sensitivity decreases with increased pool size 29 . In addition, the efficiency of the pooled tests has been reported to depend on the viral load of the samples, the dilution of the sample 30 and also the transportation mode, storage and sensitivity of the kit 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pooling samples can be challenging, and various factors can influence the sensitivity of the screening procedure. Studies have shown that sensitivity decreases with increased pool size 29 . In addition, the efficiency of the pooled tests has been reported to depend on the viral load of the samples, the dilution of the sample 30 and also the transportation mode, storage and sensitivity of the kit 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Fibre swabs are bound in layers and are not conducive to scraping epithelial cells and releasing viruses 30 . Flocked swabs are made by an electrostatic flocking process that attaches millions of nylon microfibers vertically to the swab head, facilitating sample collection, keeping the sample on the swab surface, and allowing for easier virus elution 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown RT-dPCR assays to be efficient in different samples like saliva, plasma, formalin-fixed paraffin-embedded (FFPE) tissue etc. [109][110][111] However, efforts should be made to ensure the performance characteristics of the developed dPCR assays in different sample types.…”
Section: Development and Validation Of Diagnostic Methods And Kitsmentioning
confidence: 99%
“…Furthermore, these analytical validation guidelines are compatible with different starting materials/samples like saliva, tissue, blood etc. Studies have shown RT‐dPCR assays to be efficient in different samples like saliva, plasma, formalin‐fixed paraffin‐embedded (FFPE) tissue etc 109–111 . However, efforts should be made to ensure the performance characteristics of the developed dPCR assays in different sample types.…”
Section: Applications Of Digital Pcr In Sars‐cov‐2 Quantificationmentioning
confidence: 99%